Inquiry-based teaching to develop efl students’ Critical thinking in reading comprehension - Rahmaniah Oktaviah; Nissa Mawarda Rokhman; Andi Reza Maulana (EDUCAFL : Journal of Education of English as Foreign Language, 2021)
The technology advancement in this era of globalization promotes the innovation and transformation in English language teaching and learning especially for EFL students. The innovations in English Language teaching and learning have fostered the variations of teaching strategy and method. One of the recent strategies proposed in pedagogical context is inquiry-based teaching strategy. Since the recent issues of active learning have been discussed in some school of thoughts, it is closely related to the importance of critical thinking students should have. In order to achieve English language learning goals, which is to enhance the students’ skill, competence, and also critical thinking, the teaching and learning process has to be designed more innovatively and effectively. Nevertheless, the implementation of this strategy should be adjusted in accordance to the students’ capability in learning English in class. Therefore, teachers have to understand well the characteristics of inquiry-based teaching before implementing it in class. This paper attempts to explore the use of inquiry-based teaching in promoting students’ critical thinking, especially in reading comprehension.  This paper discusses the issues of this strategy based on theoretical frameworks and provides the example of an activity using 5E that can be applied in class. The reading activity through inquiry-based teaching can be constructed by the teacher by considering the students’ condition and environment